A. Caruso & P. Saint-John : Maison dans le lincolnshire, Grande Bretagne (1999)
Vivienda que se integra al paisaje rural de la villa.
Keywords: CARUSO, A; SAINT-JOHN, P; LINCOLNSHIRE; INGLATERRA; VIVIENDAS UNIFAMILIARES